Łódzki Panel Obywatelski „Zieleń w mieście” – jak rozwijać partycypację społeczną, gdy kryzysy nawarstwiają się? - Burlińska, Agata (Public participation in urban climate policy making: The example of Lodz, 2024)
This article is an analysis of the process of the I Lodz Citizens Assembly “Greenery in the City” in the context of the two crises that were piling up when it was conducted in 2020: the climate crisis and the COVID-19 pandemic. While the climate crisis was the subject of this deliberation process, the pandemic posed a challenge in terms of the conduct and organization of the process itself. The purpose of this article is to show the added value from conducting this process, taking into account (1) the way in which the first Lodz Citizens Assembly was organized, (2) the merits of the panel – in terms of the selection of themes and the recommendations developed, and (3) the impact of the COVID-19 pandemic on both the way the panel was conducted and its substantive results. In the conclusions, recommendations were given to the public sector for the implementation of citizen assemblies on issues related to the climate crisis as well as the development of public participation during a crisis such as the pandemic.